Nuclear respiratory factor 1 promotes spheroid survival and mesenchymal transition in mammary epithelial cells. Issue 47 (22nd November 2018) - Zhou, Yuanshuai; Xu, Zhongjuan; Quan, Daniel; Zhang, Fan; Zhang, Hai; Xiao, Tongqian; Hou, Shulan; Qiao, Hong; Harismendy, Olivier; Wang, Jean; Suo, Guangli
Abstract Epithelial cells aggregate into spheroids when deprived of matrix, and the proclivity for spheroid formation and survival is a hallmark of normal and tumorigenic mammary stem cells. We show here that Nuclear Respiratory Factor 1 (NRF1) is a spheroid promoter by in silico identification of this transcription factor as highly connected to top shRNA-hits deduced from re-iterative selections for shRNAs enriched in MCF10A spheroids. NRF1-promoted spheroid survival is linked to its stimulation of mitochondrial OXPHOS, cell migration, invasion, and mesenchymal transition. Conversely, NRF1 knockdown in breast cancer MDA-MB-231 cells reduced spheroids, migration, invasion, and mesenchymal marker expression. NRF1 knockdown also reduced tumor burden in mammary fat pads and lungs of orthotopic- or tail vein-transplanted mice. With the Luminal A subtype of breast cancer, higher NRF1 expression is associated with lower survival. These results show that NRF1, an activator of mitochondrial metabolism, supports mammary spheroid survival and tumor development.